2014
DOI: 10.1186/1297-9716-45-2
|View full text |Cite
|
Sign up to set email alerts
|

Only one of the two type VI secretion systems encoded in the Salmonella enterica serotype Dublin genome is involved in colonization of the avian and murine hosts

Abstract: The type VI secretion system (T6SS) is a virulence factor for many Gram-negative bacteria. Salmonella genus harbors five phylogenetically distinct T6SS loci encoded in Salmonella Pathogenicity Islands (SPIs) SPI-6, SPI-19, SPI-20, SPI-21 and SPI-22, which are differentially distributed among serotypes. The T6SSs encoded in SPI-6 and SPI-19 contribute to pathogenesis of serotypes Typhimurium and Gallinarum in mice and chickens, respectively. Salmonella Dublin is a pathogen restricted to cattle where it causes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 28 publications
0
46
1
Order By: Relevance
“…Typhimurium (Sana et al, 2016), however, only in vivo data with CFU counts from the intestine of infected animals would allow a firm conclusion in this matter . The result is in contrast to previous reporting, where only the T6SS of S. Dublin encoded in SPI6 was shown to affect virulence, while the SPI19/T6SS was dispensable (Pezoa et al, 2014). The T6SS consists of 13 highly conserved T6SS core proteins each of which belongs to a specific COG (Boyer et al, 2009).…”
contrasting
confidence: 92%
“…Typhimurium (Sana et al, 2016), however, only in vivo data with CFU counts from the intestine of infected animals would allow a firm conclusion in this matter . The result is in contrast to previous reporting, where only the T6SS of S. Dublin encoded in SPI6 was shown to affect virulence, while the SPI19/T6SS was dispensable (Pezoa et al, 2014). The T6SS consists of 13 highly conserved T6SS core proteins each of which belongs to a specific COG (Boyer et al, 2009).…”
contrasting
confidence: 92%
“…Salmonella mutants harboring deletions of clpV or T6SS loci present defects in intracellular survival in macrophages (Haneda et al, 2009; Mulder et al, 2012; Blondel et al, 2013) and systemic colonization in mice and chicken (Mulder et al, 2012; Pezoa et al, 2013, 2014). It has been reported that bacterial pathogens like Vibrio cholerae and Burkholderia cenocepacia require specific T6SS to survive predation by D. discoideum (Pukatzki et al, 2006; Aubert et al, 2008; Zheng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the SPI-6 T6SS was first identified as a modulator of intracellular proliferation in macrophages (46,49). Recent studies further revealed that the SPI-6 T6SS is an important actor for virulence toward mice and for chicken gastrointestinal colonization (50)(51)(52). The undetectable level of T6SS expression under in vitro conditions suggests that these genes are silenced and that this silencing might be counteracted in vivo.…”
mentioning
confidence: 99%